Szkło w rzymskiej Hiszpanii – zarys problematyki - Chołuj, Aleksandra (Rzym a Półwysep Iberyjski: Różnorodność relacji od starożytności po współczesność, 2019)
Objects made of glass had appeared on the Iberian Peninsula before the Romans arrived in these areas, but only during their reign did the artefacts of this material become widespread. This was due to the introduction of a blow-molding technique, which is referred to as a ‘revolution’ in that matter. On the Iberian Peninsula, Roman glass appeared as far back as in the middle of the 1st century AD, but the state of research does not confirm its early production in this area. Written sources provide information about the glass workshops having functioned in Hispania in Antiquity, but it is not known what type they represent. Praca powstała w ramach finansowania Narodowego Centrum Nauki, projekt Harmonia 7 o nr 2015/18/M/HS3/00248